Organization of the sequences flanking immunoglobulin heavy chain genes and their role in class switching. - Tyler, B M (1980)
We have used heteroduplex analysis to investigate the sequences surrounding the germline C gamma 1 and C gamma 3 genes, and to compare them with those surrounding the C mu gene. We detected an inverted pseudogene 5' to the C gamma 3 gene and 50-65% homologous to it. A 400 bp region of the C gamma 1 and C gamma 3 3' flanking sequences was conserved as strongly as the genes (65-80%), suggesting it may have a specific function. The sequences 5' to the C gamma 1 and C gamma 3 genes and possibly also the C mu gene are composed of tandem partially homologous repeats of a similar 250 bp unit, arranged in the case of the C gamma 1 gene, in 2-5 kb blocks of alternating orientation. These repeats comprised over 13 kb of the spacer region separating the C gamma 3 and C gamma 1 genes. Recombination sites for heavy chain class switching fell within these repeated sequences, suggesting that recombination between partially homologous blocks of repeat sequences 5' to CH genes generates the deletion responsible for class switching. This hypothesis was strongly supported by an examination of published nucleotide sequences around the recombination sites of rearranged C gamma 1 and C gamma 2b genes (1,2).